(untitled) (Research, Society and Development, 2020)
Objective: To investigate the overall score and the variables associated with health literacy of pregnant women benefited from a conditional cash transfer programme. Methods: A cross-sectional survey was conducted with pregnant women benefited from a Brazilian conditional cash transfer programme. We used a validated short health literacy survey developed for research on public health and health promotion. The level of health literacy (high or low) was considered a determining variable. Descriptive, bivariate and multivariate analysis was applied to the data collected. Results: Only the two following variables were associated with health literacy: participation in health education activities and the choice of mothers to seek advice regarding pregnancy. Functional health literacy was higher when pregnant women participated in health education activities. Critical health literacy was higher when pregnant women sought advice from their mothers, friends, and other family members. Conclusion: Health education and a social network of pregnant women should be part of prenatal care.